Oriented external electric fields act as a "switch" of Pt-M/BC3N2 diatomic catalysts activate pristine ammonia borane dehydrogenation: A DFT study. (June 2022) - Huo, Jinrong; Wei, Haocong; Fu, Ling; Zhao, Chenxu; He, Chaozheng
Abstract: In this paper, the Pt-M/BC3 N2 (M= Ag, Al, Au, Co, Cr, Cu, Fe, Ir, Mn, Mo, Nb, Ni, Pd, Pt, Re, Rh, Ru, Se, Ta, Ti, V, W, Zn, La, Ce, Zr, Hf, Cd, Hg and Y) diatomic catalyst structure was constructed and used to activate Ammonia Borane (AB) under external axial electric field by the First-principles calculation method. By changing the size of applied electric field, we found that the activation of N-H bond in AB can be realized only on Pt-M/BC3 N2 (M=Al, Zn, Hf, Y) diatomic catalyst, and the effective electric field range is different. Further calculation showed that Pt-Y/BC3 N2 diatomic catalyst could not achieve the break of B-H bond. So, for Pt-M/BC3 N2 (M=Al, Zn, Hf) diatomic catalyst, further, sequentially by applying an applied electric field, we achieve the break of the B-H bond in AB and the formation of 1 mol H2 . This suggests that the electric field can act as a "switch" for activation of AB molecules. Graphical Abstract: ga1 Highlights: Construct diatomic catalysts with positron center and negative electron center. Oriented external electric fields act as a "switch" of Ammonia Borane activation. Simulate the process of Ammonia Borane dehydrogenation to H2 at room temperature. Obtain the key step reaction rate constant of Ammonia Borane dehydrogenation.